Downregulation of CD45 Signaling in COVID-19 Patients Is Reversed by C24D, a Novel CD45 Targeting Peptide - Alon, Danny; Paitan, Yossi; Robinson, Eyal; Ganor, Nirit; Lipovetsky, Julia; Yerushalmi, Rinat; Cohen, Cyrille J.; Raiter, Annat (Frontiers in Medicine, 2021)
CD45, the predominant transmembrane tyrosine phosphatase in leukocytes, is required for the efficient induction of T cell receptor signaling and activation. Various studies have demonstrated that viruses can interfere with the functions of CD45 and that patients with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) are immune-suppressed. We recently reported that the CD45-intracellular signals in peripheral blood mononuclear cells (PBMCs) of triple negative breast cancer (TNBC) patients are inhibited. We also reported that C24D, an immune modulating therapeutic peptide, binds to CD45 on immune-suppressed cells and resets the functionality of the immune system via the CD45 signaling pathway. Given the similarity between the role of CD45 in viral immune suppression, reported by others, and our findings on TNBC, we hypothesized that the C24D peptide may have a similar “immune-resetting” effect. We tested this hypothesis by comparing the CD45 intracellular signaling in PBMCs from ten COVID-19 patients versus PBMCs from ten healthy volunteers. Herein, we report our findings, demonstrating the immune reactivating effect of C24D via the phosphorylation of the tyrosine 505 and 394 in Lck, the tyrosine 493 in ZAP-70 and the tyrosine 172 in VAV-1 proteins in the CD45 signaling pathway. Despite the relatively small number of patients in this report, the results demonstrate that C24D rescued CD45 signaling. Given the central role played by CD45 in the immune system, we suggest CD45 as a potential therapeutic target.